Avaliando o papel dos valores humanos e dos estilos parentais no fenômeno do impostor: um estudo com crianças - EDUARDO FRANÇA DO NASCIMENTO (2022)
The present dissertation aimed to assess to what extent and direction human values and parenting styles are related to the imposter phenomenon in children. To achieve this goal, two manuscripts were constructed. Manuscript 1 was qualitative in nature and aimed to gather information about the relationship between impostorism and parental aspects through a systematic review. To this end, a search was conducted in the IndexPsi, PePSIC, SciELO, PsycINFO, and PubMed databases with the descriptors "imposter phenomenon," "imposter syndrome," "parenting styles," and their variations. A total of 437 articles were identified for full reading, resulting in four searches for analysis after applying the readability criteria. One theoretical study that highlighted the role of the family in childhood and its importance for the experience of impostorism in adulthood and three empirical articles were identified, with a predominance of studies that analyze parental perception and impostorism from samples composed of youth and adults. The findings allowed evidencing the relationship between impostorism and parental aspects, as well as the need for research evaluating the constructs in the national and international context. Manuscript 2 of an empirical nature, aimed to evaluate to what extent human values are related to the impostor phenomenon and parenting styles in children. Participated in this study 201 elementary school students from Campo Grande (MS), with a mean age of 10 years (SD = 1.06; ranging from 9 to 12 years), mostly female (54.5%), from public schools (97.5%), and attending the 5th (35%) year of elementary school. They answered the Child Scale of Imposter Phenomenon, Parent Perception Questionnaire-Reduced (QPP-R), Core Values Questionnaire - Child, and demographic questions (gender, age, and education). The results identified that the imposter phenomenon, correlates negatively and significantly with paternal demanding parenting style (r = -0.14) and interactive (r= -0.15) and normative (r= -0.18) values. These findings suggest the relevance of parental profile and value priorities in understanding imposterism, lacking future studies that extend the findings. In view of the findings presented in the manuscripts, it is estimated that the overall objective of this dissertation has been achieved, since the relationship between the evaluative subfunctions, parenting styles, and impostorism is identified.